The Effect of Temperature and Heating Time on The Yield and Chemical Quality of Red Fruit (Pandanus conoideus) Oil Using Dry Extraction Method - Aman, Wilson Palelingan; Sarungallo, Zita Letviany; Santoso, Budi; Murtiningrum; Paiki, Sritina N.P. (Program Studi Teknik Pertanian Universitas Hasanuddin, 2025)
The quality of Red Fruit Oil (RFO) is influenced by the extraction method. The objective of this research was to study the effect of temperature and heating time of red fruit on the chemical quality of red fruit oil using the dry extraction method. This research was divided into two steps: 1) evaluation of the chemical quality (water content, free fatty acid (FFA), iodine value, and carotenoid total) of the red fruit oil during the steaming of red fruit grains (drupa) at 60 , 80 , and 100°C for 20, 80, and 60 minutes; and 2) evaluation of the chemical quality (water content, FFA, and total carotenoids) of RFO during the steaming of red fruit chunk of whole fruit (cepallum) at 100°C for 60 minutes and 120°C for 30 minutes. The results showed that increasing the temperature and heating time of red fruit grains increased the yield (1.20 to 5.95%) and decreased the FFA levels (4.5 to 2.7%); however, the total carotenoid content of oil tended to decrease (from 7570 to 7209 μg/mL). Heating at 100°C for 60 minutes did not affect the level of saturated fatty acids in RFO. The steaming process of the red fruit chunk of whole fruit before extraction could decrease the oil yield and total carotenoid levels, as well as lower the FFA level of oil than steaming of red fruit grains.